A New Triazole-Thiol Compound Organofunctionalized on the Silica Gel Surface: Chemical Properties and Copper Sorption in Ethanol/Water Media - Magossi, Maiara S. [UNESP]; Maraldi, Vitor A. [UNESP]; Magossi, Mariana S. [UNESP]; DA Costa, Fabiola M. [UNESP]; Alves, Kamilla [UNESP]; Franco, Fernanda D. S. [UNESP]; DO Carmo, Devaney R. [UNESP] (Springer, 2020)
This study describes the preparation and characterization of 3-chloropropyl silica gel with 4-amino-5-(4pyridyl)-4H-1,2,4-triazole-3-thiol (SGA) for copper adsorption in different media. The obtained SGA material was characterized by techniques such Spectroscopy in the Infrared Region,Si-29 and(13)C Nuclear Magnetic Resonance, Scanning Electron Microscopy, X-ray Dispersive Energy Spectroscopy and Analysis of Surface Area and Porosity. The copper ion (Cu(2+))adsorption studies to the silica gel surface were performed in different media and at different temperatures. Subsequently, Langmuir and Freundlich adsorption models were applied to describe isotherm constants, wherein the most appropriate model to describe the observed adsorptive behavior was the Langmuir model. A thorough assessment of thermodynamic parameters was also carried out with the SGA material, that presented highest adsorption capacity at 45 degrees C, according to the different medias, in crescent order: water < ethanol 42% < ethanol 99%. The material SGA prepared in this word performed a high adsorption potential for Cu(2+)ions at different media and temperatures, what makes it a candidate for applications in removing and preconcentration of cupric ions from real samples, such as alcohol fuel and beverages.
Keywords: Silica gel; 4-amino-5-4(pyridyl)-4H-1; 2; 4-triazole-3-thiol; Adsorptive studies; Copper; Ethanol; water media